TISSUE DAMAGE CAUSED BY Bothrops sp ENVENOMING EVALUATED BY MAGNETIC RESONANCE IMAGING (MRI) - Fonseca, M. G.; Mathias, M. R. C. [UNESP]; Yamashita, S. [UNESP]; Morceli, J. [UNESP]; Barraviera, B. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2002)
The objective of this clinical study was to evaluate local tissue damage caused by Bothrops sp envenoming in relation to lesion type and damaged tissues using magnetic resonance imaging (MRI). Fifteen patients bitten by Bothrops snakes were treated at the Emergency Unit of the Tropical Diseases Unit at the University Hospital, Botucatu School of Medicine, UNESP, São Paulo State, Brazil. After receiving specific serotherapy, the patients were submitted to MR of the bite site. T1 spin-echo MRI were obtained revealing the following lesions: edema (n=9), edema associated with hemorrhage (n=5), and hemorrhage (n=1). Perimuscular areas (n=6) and subcutaneous tissues (n=5) were the most affected, followed by muscular tissues (n=4). It is important to mention that MRI did not show myonecrosis of the bite site, a widely reported finding in anatomical and histopathological experimental studies.
Keywords: Bothrops sp; magnetic resonance imaging; tissue damage; hemorrhage; myonecrosis